Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XVI: One new genus with one new species - Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
Based on the former examined species and new material, we described one new genus Sinagryllacris with S. cirrhatis sp. nov.. Comparing other genera of Gryllacrididae, the new genus is unique in the combination of the following characters: body slender, male ninth abdominal tergite with median hooks that are narrowly separated; female seventh abdominal sternite with 1 long process.